Pelaksanaan Kewenangan Desa Berdasarkan Hak Asal Usul Di Kecamatan Topos Kabupaten Lebong - Desi Hafizah (UNIB Press, 2024)
The purpose of enacting Law Number 6 of 2014 concerning Villages is to combine construction, namely the function of a self-government community with local self-government. It is hoped that customary law community units, In the same law, the village is given its authority, including the authority of the village based on its rights of origin, especially the villages in the Topos District of Lebong Regency. This research used an empirical legal research method. The village authority based on rights of origin according to Law Number 6 of 2014 concerning Villages in the Villages of Topos District, Lebong Regency, especially Tik Sirong Village, Suka Negeri Village, and Talang Donok I Village have similarities because they are villages that are formed from the same clan, namely the Jurukalang clan. According to Law Number 6 of 2014 concerning Villages in the Villages of Topos District, Lebong Regency, the Village authority based on rights of origin has yet to be implemented effectively. The implementation of Village authority based on rights of origin according to Law Number 6 of 2014 concerning Villages in Topos District, Lebong Regency, is hampered because (a) It is felt that limited Human Resources cannot help manage the village government system better; (b) There are no local or village regulations governing authority based on rights of origin; and (c) Traditional Institutions and Village Governments still need guidance in implementing authority in the Villages.